Ethics of Buying and Selling in the View of the Qur'an and Al-Hadith - Rosadi, Imron (Zona Law And Public Administration Indonesia, 2024)
This study analyzes the ethical principles of commerce from an Islamic perspective, grounded on Qur’an and Hadith, and their application in modern business activities. Through an in-depth analysis of primary Islamic sources and contemporary literature, this study identifies and analyzes the fundamental principles of Islamic business ethics, including the concepts of halal (al-halal), honesty (al-shidq), transparency (al-wuduh), and fairness (al-‘adalah). The research methodology uses a qualitative approach with content analysis of Qur'anic verses, Hadiths, and Islamic classical literature, as well as case studies on modern business practices. The study's findings indicate that the concepts of Islamic business ethics are highly pertinent to modern business practices and are positively associated with corporate success and sustainability. Case studies demonstrate that firms that regularly implement the principles of Islamic business ethics exhibit more sustained growth and enhanced reputations. The research indicated that the application of Islamic business principles fosters the development of a more equitable and sustainable economic structure. These findings have significant implications for the advancement of ethical and sustainable business practices in contemporary contexts, while also offering a practical framework for the application of Islamic business ethics principles in everyday operations